Periodontal disease as a predictor of chronic kidney disease (CKD) stage in older adults - Rocío Violeta Valenzuela-Narváez (Journal of International Medical Research, 2021)
Objective The aim of this study was to evaluate periodontal disease as a predictor of chronic kidney disease (CKD) stage in older adults. Methods A total of 1159 adults aged 65 to 80 years and diagnosed with periodontal disease and CKD (stages 1, 2, and 3) were randomly selected for a cross-sectional study. Periodontal status was assessed using the Community Periodontal Index of Treatment Needs (CPITN) and CKD was staged using the National Kidney Foundation Kidney Disease Outcomes Quality Initiative (NKF-KDOQI) guidelines. Results In patients with stage 1 CKD, the odds ratios (ORs) (95% confidence intervals [CIs]) for CPITN-1, CPITN-2, CPITN-3, and CPITN-4 were 1.13 (0.83–1.55), 1.47 (1.13–1.81), 1, and 1, respectively. In patients with stage 2 CKD, the ORs (95% CIs) for CPITN-1, CPITN-2, CPITN-3, and CPITN-4 were 1.49 (1.14–1.93), 1.37 (1.02–1.78), 3.07 (2.81–3.25), and 3.65 (3.49–3.71), respectively. In patients with stage 3 CKD, the ORs (95% CIs) for CPITN-1, CPITN-2, CPITN-3, and CPITN-4 were 1, 1, 4.61 (4.47–5.21), and 5.23 (5.14–5.47), respectively. Conclusion The highest CPITN values (CPITN-3 and CPITN-4) were associated with CKD stages 2 and 3. Thus, periodontal disease may be associated with progression of CKD.